REFLEKSI ATAS REVITALISASI NILAI PANCASILA SEBAGAI IDEOLOGI DALAM MENGELEMINASI KEJAHATAN KORUPSI - Taufiq, Abdullah (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2015)
The glow of corruption criminal in this country is extroudinary over limit so it needs some efforts to fight against it totally and finished. Although there are regulations for corruption act, but it doesn’t abolish yet or over come this problem, this, because the corruption has become a culturre system and rooted also become life style of the nation. So it’s rather difficult to abolish the corruption criminal via regulations.Therefore it’s need to reconstruct a nation mind set, life style, and moral by digging up the value of Pancasila as the cristalization of caracter, behaviour and personality for early Indonesian people.It is very urgent to revitalize the value of Pancasila when the nation has been suffered from bad moral, because the revitalization is real effort to reconstruct and replace the nation morality in right position as it has moved far from nation morality value that is Pancasila.A Pancasila revitalizasion is process to revitalize aboth function and occupation of Pancasila as philosophy of noble family and state. As well as make it as resource of all law resources in Indonesia country. So that Pancasila as standard, for Indonesian people in a noble family and state life.Keyword: Revitalisasi, Norma Hukum, Korupsi, Pancasila.